2020
DOI: 10.1038/s43018-019-0006-x
|View full text |Cite|
|
Sign up to set email alerts
|

L1CAM defines the regenerative origin of metastasis-initiating cells in colorectal cancer

Abstract: Metastasis-initiating cells with stem-like properties drive cancer lethality, yet their origins and relationship to primary-tumorinitiating stem cells are not known. We show that L1CAM + cells in human colorectal cancer (CRC) have metastasis-initiating capacity, and we define their relationship to tissue regeneration. L1CAM is not expressed in the homeostatic intestinal epithelium, but is induced and required for epithelial regeneration following colitis and in CRC organoid growth. By using human tissues and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
150
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(165 citation statements)
references
References 80 publications
13
150
1
1
Order By: Relevance
“…8). Intriguingly, the aggressiveness in primary tumor growth was reverted between the two cell lines, in agreement with many other reports suggesting that tumorigenesis and metastasis are unrelated phenomena (Ganesh et al, 2020;Quintana et al, 2012;Viceconte et al, 2017). This shows that the latent feature space encodes cell properties that specifically contribute to cell functions required for metastatic spreading and that these features are orthogonal to features, which allow the training of a classifier distinguishing cell lines from patient-derived melanoma models.…”
Section: Application Of Cell Type Classification To the Prediction Ofsupporting
confidence: 90%
See 1 more Smart Citation
“…8). Intriguingly, the aggressiveness in primary tumor growth was reverted between the two cell lines, in agreement with many other reports suggesting that tumorigenesis and metastasis are unrelated phenomena (Ganesh et al, 2020;Quintana et al, 2012;Viceconte et al, 2017). This shows that the latent feature space encodes cell properties that specifically contribute to cell functions required for metastatic spreading and that these features are orthogonal to features, which allow the training of a classifier distinguishing cell lines from patient-derived melanoma models.…”
Section: Application Of Cell Type Classification To the Prediction Ofsupporting
confidence: 90%
“…Intriguingly, primary tumors in MV3-injected mice grew much faster than in A375-injected mice (Fig. 8H), in contrast to being less aggressive in spreading to remote organs, suggesting that primary tumor growth is uncoupled from the ability to produce remote metastases (Ganesh et al, 2020;Quintana et al, 2012;Viceconte et al, 2017). Together, these data confirm that properties captured by feature #56 in the latent space cell descriptor define a specific gauge of the metastatic potential of melanoma that is independent of the tumorigenic potential.…”
Section: Pdx-trained Classifier Can Predict the Metastatic Potential mentioning
confidence: 52%
“…In light of the SMT's failure to explain carcinogenesis and deliver promised therapeutic successes, a third group of cancer theories has been introduced that combines a cell-based theory with elements of the tissue-based theory to explain the initial steps of carcinogenesis [36,37]. In essence, this latter group of theories retain the core of the SMT while adding the microenvironment in the form of the multiple cell types that surround the single initiating "cancer cell" [64][65][66][67][68]. They claim that either the cancer cell and its descendants "recruit" the cells in their microenvironment to "prosper" or that perturbations in the stroma induce DNA mutations and translocations in the parenchymal cells [69][70][71].…”
Section: Evaluating Theories Of Carcinogenesismentioning
confidence: 99%
“…L1CAM high population has been recently de ned as the regenerative origin of metastasis-initiating cells in colorectal cancer 19 . For further clinical insights, we reported that high expression of L1CAM, together with CXCR4, signi cantly correlated with poor overall survival in CRC patients.…”
Section: Discussionmentioning
confidence: 99%